A methoxydiphenidine-impaired driver - Stachel, Nicole; Jacobsen-Bauer, Andrea; Skopp, Gisela (International journal of legal medicine, 2016)
Methoxydiphenidine (MXP) was first reported in 1989 as a dissociative anesthetic but did not enter the market for pharmaceuticals. The substance re-appeared in 2013 as a new psychoactive substance. A case of driving under the influence of MXP is reported. The concentration of MXP has been determined from a serum sample (57 ng/mL) by liquid chromatography tandem mass spectrometry following liquid-liquid extraction. In addition, amphetamine, methylenedioxymethamphetamine, and its major metabolite were present in concentrations of 111, 28, and 3 ng/mL, respectively. The subject presented with amnesia, out-of-body experiences, bizarre behavior, and decreased motor abilities. At present, information on human toxicity of MXP is not available. MXP is comparable in structure as well as in action at the N-methyl-d-aspartate (NMDA) receptor to phencyclidine or ketamine. Therefore, it is likely that MXP exerts similar severe psychotropic action in man. However, there is no information on the duration and intensity of MXP’s impairing effects, the interpretation of a particular concentration in the blood or serum, and its detectability in routine drug screenings. Confirmation analysis may be confined to cases where the police has specific intelligence that points to MXP use.
Published online: 19 October 2015
Gesehen am 12.03.2020